The Industrial Soundscape between Fiction and Documentary Film in Italy's Long 1960s. (27th September 2018) - Cecchi, Alessandro
Abstract : During the long 1960s, which includes the culminating phase of the "economic miracle" and the beginning of the protest movement in 1968, the industrial imagination took forceful hold of the collective mind of the Italian people. While corporate films adopted the rhetoric of industrial progress, feature films offered a negative view of industrialization and underlined its problematic aspects: the exploitation of the working class, class struggle, alienation, pollution, the role of criminal enterprise. In both cases music and sound profoundly influenced the representation of the industrial contexts. Corporate films had a tendency to extol the virtues of labor and industrial production and used music extensively to this end. The wide circulation of these films in this period encouraged a critical approach to industrial contexts from feature film directors: in their films music and sound offered critical readings during the industrial sequences: they posed questions, encouraged ironic or tragic reflection, or gave the sequences grotesque or sinister overtones. This article analyzes film music and sound options in feature films against a backdrop of corporate film communication in order to trace the history of industrial imagination in Italian cinema.